The Role of ApoE Polymorphism in the Relationship between Serum Steroid Hormone Levels and Cognition in Older Chinese Adults: A Cross-Sectional Study - Huang, Xiaochen; Dong, Shengqi; Zhen, Jie; Zhang, Huiqiang; Lin, Tong; Zeng, Yuhong; Van Halm-Lutterodt, Nicholas; Yuan, Linhong (Frontiers in Endocrinology, 2018)
Background: Epidemiology studies have indicated an association of apolipoprotein E (ApoE) genetic polymorphism and circulating serum steroid hormone levels with the risk of Alzheimer’s disease (AD). The established physiologic relationship between apolipoproteins and steroid hormone indicate an important role of ApoE polymorphism in impacting the relationship between serum steroid hormones and cognition in the elderly population. Study Design: 500 Chinese adults aged between 50 and 75 participated in this community based cross-sectional study. Blood samples were collected in the morning for ApoE genotyping and serum parameter assessment. Cognitive performance of participants was evaluated by Montreal Cognitive Assessment (MoCA) test. Results: Age, gender, educational level, smoking and physical activity levels are factors associated with cognitive performance in this elderly older Chinese populationadults. Compared to the controlnormal subjects, MCI subjects demonstrated higher serum TC, HDL-C and estradiol status (P < 0.05). ApoE genotype difference of serum lipid profile was observed with a relatively higher mean serum TG levels in ApoE2 and ApoE4 carriers (P < 0.05), and lower mean serum HDL-C level in ApoE4 carriers (P < 0.05). Memory and delayed recall ability was serum estradiol level related; and subjects with higher circulating estradiol concentration exhibited lower memory and delayed recall ability (P < 0.05). The association of serum estradiol and cortisol concentration with cognitive performance was ApoE genotypes dependent. Poor cognitive performance was observed in ApoE2 and ApoE4 carriers with higher serum estradiol level (P < 0.05). Moreover, ApoE2 and ApoE4 carriers with higher serum cortisol status demonstrated decreased language ability (P < 0.05). Multiple logistic regression analysis indicates that subjects with higher serum estradiol status may susceptibly have an increased risk for MCI (OR = 2.004, 95% CI: 1.135, 3.540; P = 0.017). ApoE2 carriers with higher serum steroid levels may be potentially predisposed to an increased risk of MCI (OR = 3.353; 95% CI: 1.135, 9.907; P = 0.029). Conclusion: Cognitive outcomes in elderly older Chinese adults are associated with serum steroid hormone statesstatus. Higher serum steroid levels in ApoE2 carriers might pose an increased risk of MCI in the elderly.